Perancangan Sistem Informasi Pemesanan Tiket Travel Bengkalis (GOTralis) Berbasis Android - Farid, Muhammad; Safitri, Indah; Nabila, Nabila; Putri, Eka Susnita; Rahmayani, Mentari Tri Indah (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Technology at this time is something that is really needed to help make it easier to access everything efficiently, so an information system design has been developed which aims to make it easier for the public, especially in ordering travel tickets. So a design was built with the name GOTralis (GO Travel Bengkalis) as a means to help the public in ordering travel tickets. In this research, the author used the SDLC method, namely conducting a literature review regarding information systems, the web, SDLC, and application development tools. So this research can create a design that can make it easier for travel passengers to order travel tickets easily.